Improving Procedural Text Writing Skills Through Cooperative Learning Methods for Grade VII Students at SMP Negeri Satu Atap 5 Dusun Selatan - Ermianto Ermianto; Kastam Syamsi (Journal of Educational Sciences, 2026)
This study was motivated by the low procedural writing skills of seventh-grade students at SMP Negeri Satu Atap 5 Dusun Selatan, which were influenced by conventional learning methods that did not actively engage students. This study aimed to (1) improve the quality of the procedural writing learning process through cooperative learning methods and (2) improve students' procedural writing skills. The research used a classroom action research (CAR) design with 17 students (8 male, 9 female) as subjects and was conducted in two cycles through the stages of planning, implementation, observation, and reflection collaboratively with Indonesian language teachers. Data were collected through observation, questionnaires, and interviews, and supported by assessments of students' writing. Data analysis was conducted using qualitative descriptive methods supported by quantitative data. The results showed an increase in procedural text writing skills from the pre-cycle (score 40–58; mastery 0%), cycle I (score 59–78; mastery 35%), to cycle II (score 72–85; mastery 100%). These findings indicate that cooperative learning can increase student engagement and the quality of procedural text writing.